Optical waveguide‐based photon concentrator for hybrid photovoltaic cells. Issue 8 (9th May 2022) - Iqbal, Muddassir; Youqiao, Ma; Ullah, Sibghat; Min, Lai; Zhao, Delin; Maeda, Hiroshi
Abstract: Solar energy is pollution‐free with less impact on the ecosystem, but it has limitations due to its intermittent nature attributed to sun availability for specific hours, resulting in less energy conservation efficiency. Similar to the purpose of carvings on the leaves to collect water, we are presenting a nanometer‐thick layer of silicon or chalcogenide with fused silica for photons enhancement in red and the blue portion of the spectrum within the solar energy reaching the earth's surface. The design is based on nanorod imprints on micrometer‐sized conventional fused silica, ensuring better absorption and transportation toward hybrid photovoltaic cells. Hybrid solar cells (comprising silicon and perovskites) are typically termed the future of solar power, but will not be discussed here. Effective area, optical power concentration, and second‐ and higher‐order dispersions can further help design and develop the photon concentrators.